ANALISIS PERUBAHAN SUKU BUNGA , UANG DAN HARGA DALAM KERANGKA KERJA EKONOMI KLASIK - Tahwin, Muhammad (potensio, 2009)
According to classical economic experts, interest rates aredetermined by the wishes of the people to make savingsand the desire of the entrepreneur to borrow funds for capitalinvestment. Flexibility in interest rates would bring the statein which the amount of savings realized in the economy atfull employment is achieved when is equal to the investmentthat would be entrepreneurs. But now it turns out that thecommunity income level also determines the level ofsavings. The higher the income, the higher the savings.According to the theory that the added quantity of moneysupply will cause the same percentage price increase withincreasing money supply. While in theory the remaining cashthat the accretion of money supply will raise prices on thesame level with the added supply of money.Keyword: Interest, Money, and Price